Bargaining over strategies of non-cooperative Games - Giuseppe Attanasi; Aurora García-Gallego; Nikolaos Georgantzís; Aldo Montesano (Games, 2015)
We propose a bargaining process supergame over the strategies to play in a non-cooperative game. The agreement reached by players at the end of the bargaining process is the strategy profile that they will play in the original non-cooperative game. We analyze the subgame perfect equilibria of this supergame, and its implications on the original game. We discuss existence, uniqueness, and efficiency of the agreement reachable through this bargaining process. We illustrate the consequences of applying such a process to several common two-player non-cooperative games: the Prisoner's Dilemma, the Hawk-Dove Game, the Trust Game, and the Ultimatum Game. In each of them, the proposed bargaining process gives rise to Pareto-efficient agreements that are typically different from the Nash equilibrium of the original games.
Keywords: C72; C73; C78; 330; bargaining; supergame; confirmed proposals; confirmed agreements